Curricular diversification of learning experiences and the development of competencies - Hidalgo-Concepción, Bersy A. (2023)
Curricular diversification, a task inherent to the teacher, has been carried out for many years, this action that seeks to ensure in basic education students a broader, general, versatile training, whose process responds to the characteristics, needs, interests, individual potentialities or of a group of students in a given context. Given this situation, curricular diversification is proposed, a process that seeks to guarantee the relevance and relevance of education in our country. On the other hand, learning experiences constitute the development of activities that present situations for the student to address the significant situation, they are articulated around that purpose. When the student can act in relation to that significant situation, he has developed competencies. The curricular diversification is based on guidelines that seek to establish guidelines that guarantee the understanding and realization of the curricular diversification, in a planned and participatory manner. The research corresponds to the descriptive bibliographic method.